Моделювання роботи важільних механізмів на базі центрального прямолінійно напрямного кривошипно-повзунного механізму у SolidWorks - Міняйло, Петро (Видавництво Львівської політехніки, 2013)
The simulation of straight-line mechanisms and dwell mechanisms on the basis of slider-crank mechanism in SolidWorks is viewed. Straight-line mechanisms, which is widely used in modern engineering, describe the rod curve that in a particular area is close to a straight line, which provides a dwell of the final link of mechanism. Graphs for the kinematic parameters of dwell mechanisms are shown. The main aim of the research – to simulation the mechanisms and test their kinematic parameters. As seen from the results, the use of modern CAD systems such as SolidWorks, allows you to check all the necessary parameters based on computer models of mechanisms and significantly simplify experimental study of physical models of mechanisms and machines.
Keywords: прямолінійно напрямний механізм; механізм із зупинкою; тривалість зупинки; комп’ютерне моделювання; SolidWorks; SolidWorksMotion